Role of microRNAs in antiviral responses to dengue infection - Wong, Rui Rui; Noraini Abd Aziz, *; Sarah Affendi,; Poh, Chit Laa * (BMC, 2020)
Dengue virus (DENV) is the etiological agent of dengue fever. Severe dengue could be fatal and there is currently no effective antiviral agent or vaccine. The only licensed vaccine, Dengvaxia, has low efficacy against serotypes 1 and 2. Cellular miRNAs are post-transcriptional regulators that could play a role in direct regulation of viral genes. Host miRNA expressions could either promote or repress viral replications. Induction of some cellular miRNAs could help the virus to evade the host immune response by suppressing the IFN-α/β signaling pathway while others could upregulate IFN-α/β production and inhibit the viral infection. Understanding miRNA expressions and functions during dengue infections would provide insights into the development of miRNA-based therapeutics which could be strategized to act either as miRNA antagonists or miRNA mimics. The known mechanisms of how miRNAs impact DENV replication are diverse. They could suppress DENV multiplication by directly binding to the viral genome, resulting in translational repression. Other miRNA actions include modulation of host factors. In addition, miRNAs that could modulate immunopathogenesis are discussed. Major hurdles lie in the development of chemical modifications and delivery systems for in vivo delivery. Nevertheless, advancement in miRNA formulations and delivery systems hold great promise for the therapeutic potential of miRNA-based therapy, as supported by Miravirsen for treatment of Hepatitis C infection which has successfully completed phase II clinical trial.